Land Pedagogy Resurgence - First Nations Education during the Pandemic - Woroniuk, Lillian (Scholarship@Western, 2021)
This paper examines First Nations peoples’ educational experiences during the Covid 19 pandemic, including their engagement with land-based pedagogy. First Nations peoples have always had a deep connection and reciprocal relationship with their ancestral lands. Within Eurocentric school settings, many First Nations students are systemically disadvantaged, and their knowledge systems are often undermined. This paper focuses on the critical importance of how First Nations peoples draw on land pedagogy and center their Indigenous knowledge to continue their formal and informal learning during the pandemic. I have chosen to restrict the literature review to Canadian content as my research is focused on pandemic impacts with First Nations schools and includes First Nations peoples in relation to informal land-based education practices at the community level. Drawing on existing literature, my research question will look at how and in what ways have First Nations peoples engaged in land-based pedagogy during the pandemic? This paper will make use of secondary sources including gray literature. https://ir.lib.uwo.ca/headandheartprogram_2021/1008/thumbnail.jpg